2021
DOI: 10.3390/biology10060509
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Behavior and Complications of Intentionally Tilted Dental Implants Compared with Straight Implants Supporting Fixed Restorations: A Systematic Review and Meta-Analysis

Abstract: The aim of this study was to assess the long-term clinical behavior of straight implants in comparison with intentionally tilted dental implants (ITDI) supporting fixed restorations in partial or total edentulous arches, analyzing implant survival and success rates, complications, and marginal bone loss (MBL) after >5 years of function. An electronic search was conducted in five electronic databases (MEDLINE/Pubmed, Embase, Web of Science, Scopus, and Cochrane Central Register of Controlled Trials) suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[20,21] When alveolar bone have defects, in the absence of bone graft technology, inclined, narrow or short implants may also be considered. [22][23][24] Narrow-diameter implants have also been proved to be one of the solutions for two-way bone defects in the clinical application guidelines for International Team for Implantology (ITI), [25] it shows that the mandibular second molar area bears a large chewing pressure, and the implant width is preferably ≥4.1 mm and the length is ≥8 mm. [26] Otherwise, the implant is prone to fracture when the chewing function is exerted.…”
Section: Discussionmentioning
confidence: 99%
“…[20,21] When alveolar bone have defects, in the absence of bone graft technology, inclined, narrow or short implants may also be considered. [22][23][24] Narrow-diameter implants have also been proved to be one of the solutions for two-way bone defects in the clinical application guidelines for International Team for Implantology (ITI), [25] it shows that the mandibular second molar area bears a large chewing pressure, and the implant width is preferably ≥4.1 mm and the length is ≥8 mm. [26] Otherwise, the implant is prone to fracture when the chewing function is exerted.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported fracture of anterior acrylic teeth more than posterior ones. Incidence of the tooth fracture varies in the studies from low incidence to a frequent ones that may be due to the different follow-up periods or patient's behaviors [34].…”
Section: Discussionmentioning
confidence: 99%
“…To engage basal bone, as reported by several authors, tilted implants could represent a possible solution also in rehabilitation of totally edentulous maxilla with severe atrophy of the posterior sectors, avoiding more invasive techniques and allowing immediate loading [43][44][45].…”
Section: Discussionmentioning
confidence: 99%